Strategic Intelligence: The Cognitive Capability to Anticipate Competitor Behavior - Levine, Sheen S.; Bernard, Mark; Nagel, Rosemarie (Strategic Management Journal, 2017)
Research summary: Pursuing sources of entrepreneurial and competitive advantage, researchers have been exploring cognition. We examine how cognitive capabilities affect competitive performance, drawing on two constructs rooted in psychology and economics. A familiar one is analytic skill, the ability to solve abstract problems. To that, we add strategic intelligence — the ability to anticipate competitors' behavior and preempt it. Using incentivized experiments, we measure the constructs in participants, then let them compete for cash in a highly competitive market. Although the market is designed to eliminate any advantages, whether from market structure or strategic resources, some profit much more than others. We trace performance differences to heterogeneity in analytic skill and strategic intelligence, and show how the two fuel superior performance, even against tough competition . Managerial summary: Why do some entrepreneurs outperform others? How can companies succeed against tough competition? Certainly, some benefit from unique resources, such as patents, and others can winnow competition, as through mergers. But some have entered highly competitive markets, lacking obvious resources, yet managed to achieve impressive success: think Under Armour, Wal‐Mart or Home Depot. Here we test how advantage can stem from managerial cognition. We measure two kinds of cognitive skill in market participants, and then let them vie for cash in intensely competitive markets. Some end up with far more profit than others. Tracing the root of high performance, we find it is predicted by a combination of analytic skills, the ability to solve abstract problems, and strategic intelligence—ability to anticipate competitors' behavior and preempt it . Copyright © 2017 John Wiley & Sons, Ltd. Resources This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available at http://doi.org/10.17605/OSF.IO/P49YA . Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki .